O potencial da realidade virtual e aumentada na concepção de objeto de visualização para aprendizagem de Física - França, Carlos Roberto (2019)
Since the emergence of the Internet in Brazil in the mid-90's until the present day, what is seen are new computational tools and forms of communication and interaction in all media and social strata. Of course, the processes involving teaching and learning have been affected by this sea of technological possibilities. In this scenario, the research presents the potential of Virtual and Augmented Reality in the conception of a visualization object for learning of Physics, with the contributions of Cognitive Load Theory and Visualization in science teaching. Information is provided. We present the theoretical references adopted in this research and, finally, the process of creation and conception of a computational tool dedicated and thought for the teaching of physical greatness angular momentum. The digital resource, RVA_360 - Momento Angular, was made available in two versions of Virtual and Augmented Reality. One in the immersive mode using the Oculus Rift platform and the other in the semi-immersive mode for various computing platforms. The research brings to light their contributions to the engagement of new developers and researchers in the areas of teaching-learning physics and in the production of educational computational resources. The opinions collected during the tests and validations phase of the tool are discussed and discussed, which were done by teachers of higher education physics. Finally, the research presents the contributions to the teaching-learning processes of angular momentum, through a three-dimensional immersive environment that the RVA_360 tool makes available to users.